Metabolic effects and biotransformation of perfluorohexyloctane in human hepatocytes - Alijagic, Andi; Chaker, Jade; Barbosa, João Marcos G.; Duberg, Daniel; Castro-Alves, Victor; Dickens, Alex M.; Orešič, Matej; Hyötyläinen, Tuulia (Elsevier, 2026)
Perfluorohexyloctane (F6H8) is a semifluorinated alkane recently approved for ophthalmic treatment of dry eye disease. Although considered locally safe for topical use, its structural similarity to persistent per- and polyfluoroalkyl substances (PFAS) raises concerns about systemic accumulation and long-term toxicity. To investigate potential hepatic effects, we examined the metabolic impact of F6H8 exposure in human HepaRG hepatocytes across a broad concentration range representing short- and long-term exposure scenarios. Combined targeted and untargeted metabolic profiling by ultra-high-performance liquid chromatography–quadrupole time-of-flight mass spectrometry (UHPLC-QTOFMS) was performed on intracellular extracts and extracellular media. F6H8 induced pronounced, concentration-dependent metabolic alterations, many of which exhibited non-monotonic responses. Low concentrations primarily affected amino acid, fatty acid, and lipid metabolism, while central carbon metabolism was disrupted only at the highest exposures. Notably, a putative biotransformation product, perfluorohexyloctanoic acid, was detected, suggesting metabolic persistence and conversion to a PFAS-like structure. This metabolite showed strong associations with cellular metabolic profiles and elicited metabolic changes that only partially overlapped with those induced by the parent compound, indicating distinct biological activity following biotransformation. These findings indicate that F6H8 elicits broad metabolic reprogramming and may not be metabolically inert as previously assumed. Given its clinical use and structural similarity to persistent fluorochemicals, the results highlight the need for comprehensive, long-term safety assessment of F6H8 and related semifluorinated alkanes.